2021
DOI: 10.3389/fonc.2021.634075
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Novel Biomarkers Related to M2 Macrophages Infiltration by Weighted Gene Co-Expression Network Analysis in Prostate Cancer

Abstract: M2-tumor-associated macrophages (TAMs) work as a promoter in the processes of bone metastases, chemotherapy resistance, and castration resistance in prostate cancer (PCa), but how M2-TAMs affect PCa has not been fully understood. In this study, we analyzed the proportion of tumor-infiltrating immune cells using the CIBERSORT algorithm, based on samples from the Cancer Genome Atlas database. Then we performed weighted gene co-expression network analysis to examine the modules concerning infiltrated M2-TAMs. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In general, as the number of somatic mutations in a tumor increase, the ability to generate neoantigens increases. It was also observed that the tumor neoantigen load could be efficiently determined by analyzing the TMB [ 32 ]. MSI is a robust mutant factor phenotype, the generation of which can be attributed to the presence of defects in mismatch repairing of DNA.…”
Section: Discussionmentioning
confidence: 99%
“…In general, as the number of somatic mutations in a tumor increase, the ability to generate neoantigens increases. It was also observed that the tumor neoantigen load could be efficiently determined by analyzing the TMB [ 32 ]. MSI is a robust mutant factor phenotype, the generation of which can be attributed to the presence of defects in mismatch repairing of DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The Cell-type Identification by Estimating Relative Subsets of RNA Transcripts (CIBERSORT) analysis with the “CIBERSORT” R package was applied to estimate the fractions of 22 immune cell types in all BC patients ( 21 ). Briefly, after filtering out genes with an average expression of 0, the proportion of multiple immune cells in normalized mRNAseq data was quantified using the leukocyte gene signature, termed LM22.…”
Section: Methodsmentioning
confidence: 99%
“…The corration of Immune cell type and risk group was according to the immune infiltrates scores based on CIBERSORT, XCELL, TIMER and MCPCOUNTER algorithms were retrieved from TIMER 2.0 database (http://timer.cistrome.org/). The Cell-type Identification by "CIBERSORT" R package was applied to estimate the fractions of 22 immune cell types in all PAAD patients (26).…”
Section: Immune Cell Infiltration Analysis and Cancer-immunity Cyclementioning
confidence: 99%